CULTURAL HERITAGE PRESERVATION AS A COMPONENT OF CULTURAL POLICY: A GLOBAL VIEW - Біловус, Леся Іванівна; Гомотюк, Оксана Євгенівна (My University, 2022)
Ukraine’s ratification of the most authoritative UNESCO and Council of Europe Conventions draws attention to issues of cultural heritage protection implementation of their provisions in the state’s monument protection practice. In Ukraine, there is a lack of understanding of the social mission of culture, a poorly developed non-state sector, institutions of criticism, curatorship, and a low level of communication between environments; the management function is limited to the distribution of resources, there are no legal definitions related to the sphere of culture; there is a shortage of competent professional managers of culture, as well as relevant educational programs that would educate an active consumer of a cultural product. The purpose of the study is to study international experience in improving the national cultural policy in the field of cultural heritage protection, as well as to determine the level of compliance of the monument protection system of Ukraine with international standards in the context of European integration processes. The study examines the management system of cultural heritage objects in the context of national legislation in the culture and aspirations of the Ukrainian state to meet the requirements of European regulations. The critical problem of the modern national system of management of historical immovable objects of cultural heritage is determined to be large-scale Russian aggression, which is a gross violation of international law and an attack on human rights and fundamental values and principles of the EU. This war of mentalities sharpened attention to cultural policy and European values and identified Ukraine’s weak points in this area. Therefore, close cooperation with UNESCO and the help of partners from European countries are becoming urgent. For the Ukrainian state, it is essential to form a single national cultural space as the basis of social consolidation, as part of the European cultural space, the affirmation of European democratic values, the effective use in the interests of society of the creative potential of Ukrainian artists, and the preservation of the national historical and cultural heritage. It is essential to understand “European standards” in the cultural sphere, their implementation in the Ukrainian humanitarian space, the unity of the intercultural diversity of Ukrainian regions, and the reconciliation of their vision of Ukraine’s past and future.
Keywords: cultural heritage, preservation of cultural heritage, intercultural communications, European Union, European identity